Motivation for the activation of pintar parliament portal toward open & digital government in parliamentary affairs department of MCMC - Mahat, Faizul Azlee (2022)
It is a known fact that electronic records and digital records are widely replacing paper records; hence, proper storage is a must for future references. This paves the way for the creation of novel theoretical record-keeping models, newer electronic record-keeping standards, and the ever-evolving development of electronic record-keeping technologies to be used internally in organisations. The usage rate, acceptance and implementation of electronic record keeping solutions by end-users vary significantly, and it has become a problem. This could be attributed to the legal requirements, the exponential increase of electronic records, and the implication of trustworthy electronic record keeping to individuals, organisations, and societies. Subsequently, this study aims to address the issue above by determining the variables that impact users" decision to utilise an electronic record-keeping system. A crucial task in any research project is defining its core objectives or questions. In order to achieve the objectives of the study, this research has employed a mix method research strategy and with help the help of previous study, observation, analysis, comparison and reasoning. Significant amount of research has been dedicated to studying the systems used in various situations. A survey instrument was developed and administered to a selected sample of employers from the Communication and Multimedia Commission (“MCMC”). This is done in order to evaluate the research model quantitatively and to determine the relative importance of the factors. By identifying the factors that impact the use of electronic record-keeping systems, this research will inform future strategies to improve the capture and retention of our digital heritage. Finally, establish connections between organizational processes and knowledge activities is critical for gaining a competitive edge and securing agency credibility.